Correlation of HCV Infection and Creatinine Levels in Thalassemia Patients - Al-Moussawi, Duaa K. (University of Thi-Qar Journal of Science, 2022)
The current investigation was conducted at the Center for Genetic Blood Disorders (on thalassemia). Between December 2019 and February 2020. Their ages range from one to forty. They have an past, thalassemia-ridden, with high creatinine levels. Tubes without EDTA were used to collect blood samples from 20 thalassemia individuals who had no kidney problems. a control group, a history of normal creatinine levels, and a restricted age range of 1 to 40 years. There are 120 patients total across the two groups, and all samples were used for the RT-PCR, creatinine level, and HCV ELISA test. The current study found that 20 of 120 individuals without kidney problems and 100 of 120 individuals with kidney defects both had HCV infections. Kidney disease is diagnosed by first determining the creatinine level, followed by ELISA and to determine the presence of IgM and IgG in the patient’s serum. Creatinine levels in men are higher than those in women. The age group of 21–31 years in this study had more kidney defect instances (11) out of 100 (85%) than any other age group, according to the random sample size of the kidney defect group. (The age group of 21-31 was (0.63%) older than the age group of 20. The age group of 21–31 years in the normal kidney group (control group) was older than the group of 3–20 years (0.63%).